2017
DOI: 10.3847/1538-3881/aa947e
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Properties of the Pulsating Post-mass Transfer Eclipsing Binary OO Draconis

Abstract: OO Dra is a short-period Algol system with a δ Sct-like pulsator. We obtained timeseries spectra between 2016 February and May to derive the fundamental parameters of the binary star and to study its evolutionary scenario. The radial velocity (RV) curves for both components were presented, and the effective temperature of the hotter and more massive primary was determined to be T eff,1 = 8260 ± 210 K by comparing the disentangling spectrum and the Kurucz models. Our RV measurements were solved with the BV ligh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 46 publications
2
10
1
Order By: Relevance
“…Thus, we adjusted the rotation parameter of F 1 = v 1,rot / v 1,sync = 0.68 in the binary modeling, and the resulting binary solutions are coincident with those of F 1 = 1.0 within their uncertainties. As in the case of OO Dra (Lee et al 2018) and V404 Lyr (Lee et al 2020), the parameter of rotation rate F indicated a weak sensitivity in this binary solution.…”
Section: Binary Modeling and Absolute Dimensionssupporting
confidence: 55%
“…Thus, we adjusted the rotation parameter of F 1 = v 1,rot / v 1,sync = 0.68 in the binary modeling, and the resulting binary solutions are coincident with those of F 1 = 1.0 within their uncertainties. As in the case of OO Dra (Lee et al 2018) and V404 Lyr (Lee et al 2020), the parameter of rotation rate F indicated a weak sensitivity in this binary solution.…”
Section: Binary Modeling and Absolute Dimensionssupporting
confidence: 55%
“…Struve (1946) reported that his results were not fully exempted from rotational broadening and line blending between the components. Trailed spectra are of great use in revealing and tracking the orbital motions of binary stars (e.g., Lee et al 2018Lee et al , 2020aLee et al , 2020b. In order to look for sets of absorption lines for X Tri, we made the phase-folded trailed spectra from the BOES observations and examined them in detail at full wavelength.…”
Section: New Spectroscopy and Data Analysismentioning
confidence: 99%
“…To validate the ICC approach, this study revisits two wellknown objects, δ Sct-type pulsating primary stars in the doublelined eclipsing binary systems AB Cas 1 and OO Dra. These two δ Sct primaries differ from classical δ Sct stars in evolutionary terms due to mass transfer between the binary components (Hong et al 2017;Lee et al 2018;Mkrtichian et al 2022); their binary evolution is described in Section 5.2. They have an important advantage from an asteroseismic aspect in that their physical properties, such as masses and radii, are well constrained from photometric and spectroscopic observations.…”
Section: Introductionmentioning
confidence: 99%